Development of an automated pre-processing tool and case study for coach rollover analysis. (1st January 2013) - Li, Y.; Lan, F.C.; Chen, J.Q.
Coach rollover numerical simulation is a highly complex and time-consuming process, especially in terms of its pre-processing tasks, which are commonly done manually. To improve modelling effi ciency and standardise the modelling process so as to shorten the computation running time, based on the fi nite element software package Altair HYPERWORKS, an automated process tool is developed using Tool Command Language (TCL). The tool's framework is proposed as a step-by-step modelling wizard including 12 technical modules in compliance with ECE/R66. Users can easily use the tool without specialised knowledge of rollover simulation process and regulations. Based on the wizard, the complete fi nite element modelling for a coach rollover simulation validates the process tool's capability in automation and effi ciency. Then a case study of coach rollover is carried out to investigate the rollover scenario and the superstructure strength. Compared to previous pre-processing methods, remarkable time was saved and the modelling process was standardised by utilising the automated process tool, which proved its feasibility and high effi ciency.